Pengaruh Model Altman Z-Score Terhadap Financial Distress Pada Bank Perkreditan Rakyat Provinsi Kalimantan Barat - Pertiwi, URAY MAHARANI Pertiwi B1021141111 (Jurnal Manajemen Update, 2018)
Financial distress is the company's financial condition in the stage of decline before liquidation or bankruptcy of the company (Ali, 2009). In general, financial distress is a condition where companies experience financial difficulties and are threatened with bankruptcy. Then the condition of financial distress needs to be watched out for the company.This study aims to examine the effect of the Altman Z-SCORE ratio, namely the ratio of Net Working Capital to Total Assets (WCTA), Retained Earning to Total Assets (RETA), Earning Before Interest and Tax to Total Assets (EBITTA), and Book Value of Equity to Total Liability (BVETL) to Financial Distress proxied by Z-Score Modification at the Rural Bank of West Kalimantan Province and to find out the condition of financial distress in each bank calculated by the modified Altman Z-score method. This study took a five-year observation period, from 2012 to 2016, where the number of samples used was as many as 15 companies crediting the rural banks of West Kalimantan Province. This study examines the regression relationship between the dependent variable and the independent variable with multiple linear regression. In this study showed that the partial test results of the ratio found in the modified Altman Z-score, WCTA, RETA, EBITTA and BVETL had a significant positive effect on financial distress.Keywords : Financial Distress, Z-Score, BPR, WCTA, RETA, EBITTA, BVETLÂ DAFTAR PUSTAKAAltman,E.I.1968.â€œFinancial Ratios,DiscriminantAnalysisandThePrediction of Corporate Â Â Â Â Â Â Â Â Â Â Â Â  Bankruptcyâ€. The Journalof Finance Vol.XXIIINo. 4, September1968.Â Almilia,Luciana SpicadanKristijadi. (2006).AnalisisRasioKeuanganuntukMemprediksiKondisiFinancialDistress Perusahaan manufaktur yang terdaftar di BEJ .Jurnal Akuntansi dan Auditing Indonesia,Vol.7No. 2.Â Endri.(2009). Prediksi Kebangkrutan Bank untuk menghadapi dan mengelola Perubahan Â Â Â Â Â Â Â Â Â Â  lingkungan bisnis: Analisis Model Altmanâ€™s Z-Score.Jurnal Perbanas Quarterly Review, Â Â Â Â Â Â Â Â Â  Vol. 2. No. 1.Â Sofiasani , G. & Gautama, B.P. (2016). Pengaruh CAMEL Terhadap FinancialÂ  Distress Pada Â Â Â Â Â Â Â Â Â  Sektor Perbankan Indonesia, Journal of Financial Business Management and Â Â Â Â Â Â Â Â  Eunterpreneurship Education, Volume1,No.1.Â Irfan, M & Tri Yuniati. 2014. Analisis Financial Distress DenganPendekatan Altman Zâ€- Score Untuk Memprediksi Kebangkrutan Perusahaan Telekomunikasi. Jurnal Ilmu & Riset Akuntansi. Vol. 3. No. 1.Â Institut Bankir Indonesia.1999.Kamus Perbankan Indonesia. JilidDua.Â Almilia.2004.Analisis aktor-Faktor Yang Mempengaruhi Kondisi Financial Distress Suatu Perusahaan Yang Terdaftar di BEJ. Jurnal Riset Akuntansi Indonesia. Vol. 7. No. 1.Â Brigham & Houston (2010), DasardasarManajemen Keuangan. Jakarta: Salemba Empat.Â Platt & Platt. 2006. Understanding Differences Between Financial Distress and Bankruptcy. Review of Applied Economies. Vol. 2, No. 2.Â Platt, & M.B. Platt. Predicting Financial Distress. Journal of Financial Service Profesionals,56, Hlm. 12-15.Â Institut Bankir Indonesia.1999.Kamus Perbankan Indonesia.Jilid Dua.Â Wilopo.2001.â€œPrediksi Kebangkrutan Bankâ€.Jurnal Riset Akuntans Indonesia, Vol.4,No. 2, Â Â Â Â Â Â Â Â Â Â Â Â  Mei2001:184-198.Â Undang-Undang RI No 10 Tahun 1998 tentang Perbankan,Jakarta:Penerbit PT Sinar Grafita.Â Dendawijaya,M. D. (2003). ManajemenPerbankan.Jakarta:Ghalia Indonesia.Â Sugiyono. (2003). Metode Penelitian Pendidikan Pendekaran Kuantitatif, Kualitatif,Â  dan R&D. Â Â Â Â Â Â Â Â Â Â Â Â Â  Bandung: ALFABETA.Sugiyono. (2005). Metode Penelitian Pendidikan Pendekaran Kuantitatif,Kualitatif, danR&D. Â Â Â Â Â Â Â Â Â Â Â  Bandung: ALFABETA.